Overlapping Music Royalty Sanctions in Public Spaces: An Analysis of Indonesian Legal Politics - Sakundiana, Vita Dwi; Alatas, Lulu Syakirah; Permatasari, Desi (UIN Sunan Kalijaga Yogyakarta, 2025)
The use of music in public spaces continues to increase alongside the development of the entertainment, tourism, and marketing industries, at both the national and international levels, making the management of music royalties a strategic issue in copyright governance. Many previous studies have focused solely on law enforcement effectiveness or compliance with royalty payments, without examining in depth the legal politics underlying the disharmony between public legal norms and contractual mechanisms for royalty management. This study aims to analyze the direction of legal politics in managing music royalty sanctions in the public space, as set out in Law Number 28 of 2014 concerning Copyright (the Copyright Law) and contracts managed by the National Collective Management Institute (LMKN). The method used is a normative juridical approach that analyzes the Copyright Law and applies the principle of distributive justice, drawing on primary and secondary legal materials. The results of the study show that the overlap of sanctions is caused by the absence of a clear legal-political design for placing LMKN contracts as hierarchically integrated instruments within public legal norms, thereby creating legal uncertainty, potential duplication of sanctions, and weak governance of royalty distribution. The novelty of this research lies in its analysis of legal politics in the relationship between public norms and private contracts in the music royalty system, which makes a conceptual contribution to harmonizing sanctions and renewing copyright policies in the era of the digital creative economy.